Pelatihan dan Asistensi Penulisan Ekspresi Matematis Dengan Bantuan Microsoft Word Bagi Calon Guru Di STKIP Melawi Kampus Perbatasan Entikong - Vera Riyanti; Yuli Budhiarti; Samsul Bahri (Universitas 45 Surabaya, 2023)
Skills and fluency of students or prospective teachers in using Microsoft Word application are highly demanded to ensure the successful completion of tasks. The issue at hand is that the majority of students lack sufficient proficiency in typing mathematical formulas into Microsoft Word documents. The purpose of this training and assistance activity is to help enhance the knowledge and share experiences with prospective teacher students regarding writing mathematical expressions in Microsoft Word. The method employed in this training activity involves the demonstration of materials and direct practice and exercises by the participants. Based on the results of the activity, out of the 12 participants, 10 were able to practice without direct assistance, while 2 still needed direct guidance and support. Consequently, it can be concluded that most of the prospective teacher students already understand how to write mathematical expressions in Microsoft Word but still need to practice to improve their fluency.